1971
DOI: 10.1172/jci106465
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II in arterial and renal venous plasma and renal lymph in the dog

Abstract: A B S T R A C T Angiotensin II was determined by radioimmunoassay in systemic arterial, pulmonary arterial, and renal venous plasma and in renal hilar lymph in dogs. Levels of the peptide were determined prior to and during progressive graded hemorrhage or reduction in renal perfusion pressure. Levels of angiotensin II in plasma consistently rose during transit through the lung indicating pulmonary conversion of angiotensin I to angiotensin II. On the other hand, angiotensin II in the renal vein plasma was les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(46 citation statements)
references
References 14 publications
3
43
0
Order By: Relevance
“…Earlier measurements of renal lymph, considered a reflection of renal interstitial fluid, suggested that interstitial fluid Ang II concentrations were much higher than plasma concentrations. [45][46][47] These results were consistent with the notion that Ang II is formed locally and added to the interstitial compartment. However, it was not clear how much of renal lymph Ang II concentrations were due to continued Ang II formation within the lymphatic compartment, since lymph also contains ample quantities of renin and renin substrate.…”
Section: Intrarenal Levels Of Angiotensin IIsupporting
confidence: 85%
“…Earlier measurements of renal lymph, considered a reflection of renal interstitial fluid, suggested that interstitial fluid Ang II concentrations were much higher than plasma concentrations. [45][46][47] These results were consistent with the notion that Ang II is formed locally and added to the interstitial compartment. However, it was not clear how much of renal lymph Ang II concentrations were due to continued Ang II formation within the lymphatic compartment, since lymph also contains ample quantities of renin and renin substrate.…”
Section: Intrarenal Levels Of Angiotensin IIsupporting
confidence: 85%
“…Danser et al demonstrated rapid ANG I degradation within the cardiac and systemic vasculature of the pig in vivo, and an increased ANG I degradation rate during captopril administration, most likely due to aminopeptidase and endopeptidase action on increased concentrations of ANG I substrate (35). Previous studies by Bailie et al demonstrated that, after injection into the renal artery of the dog, significant amounts of 14 C ANG II did not appear in the renal lymph or the urine, suggesting that metabolism of circulating ANG peptide occurs primarily in the vascular compartment (36). In a related fashion, the endothelial cell has been shown to metabolize very actively adenosine, and thus function as a physiological barrier for passage of adenosine into the ISF (37).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it has recently been demonstrated that the majority of angiotensin I found in renal venous blood is of intrarenal origin (35). Evidence for predominent intrarenal production of angiotensin II has been suggested by the demonstration that angiotensin II concentrations in the renal lymph (36), and the proximal tubule (37) greatly exceeded the plasma concentrations. A body of data suggests that the intrarenal RAS may be involved in the alterations in sodium and fluid balance observed in chronic HF via direct tubular effect or hemodynamic changes ( 19,38).…”
Section: Discussionmentioning
confidence: 99%